Editorial: plant-microbial symbiosis toward sustainable food security - Ixchel Campos-Avelar; Amelia C. Montoya-Martínez; Fannie I. Parra-Cota; Sergio de los Santos-Villalobos (Plant Signaling & Behavior, 2024)
The use of plant-associated microorganisms is increasingly being investigated as a key tool for mitigating the impact of biotic and abiotic threats to crops and facilitating migration to sustainable agricultural practices. The microbiome is responsible for several functions in agroecosystems, such as the transformation of organic matter, nutrient cycling, and plant/pathogen growth regulation. As climate change and global warming are altering the dynamics of plant-microbial interactions in the ecosystem, it has become essential to perform comprehensive studies to decipher current and future microbial interactions, as their useful symbiotic mechanisms could be better exploited to achieve sustainable agriculture. This will allow for the development of effective microbial inoculants that facilitate nutrient supply for the plant at its minimal energy expense, thus increasing its resilience to biotic and abiotic stresses. This article collection aims to compile state-of-the-art research focused on the elucidation and optimization of symbiotic relationships between crops and their associated microbes. The information presented here will contribute to the development of next-generation microbial inoculants for achieving a more sustainable agriculture.